A Review for Usefulness of Atypical Antipsychotics and Cholinesterase Inhibitors in Delirium - Tahir, T. A. (Pharmacopsychiatry, 2012)
Although the information from Gover et al (2011) is comprehensive it does not include vital information for management of delirium from key studies in this area of research. This paper has summarised information as lists and tables without systematic critical appraisal. Therefore, in the absence of a robust methodology for literature search and critical appraisal of past and current literature, it has limited implications to help future management or research in the field of delirium.
Keywords: acetylcholinesterase; delirium; dopamine antagonist; antipsychotic drugs; quetiapine